2014
DOI: 10.1080/01652176.2014.962116
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolic profiling of dairy cows affected with clinical ketosis using LC/MS technology

Abstract: Our results showed that the metabolic changes in cows with clinical ketosis involve complex metabolic networks and signal transduction. These results are important for future studies elucidating the pathogenesis, diagnosis, and prevention of clinical ketosis in dairy cows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 31 publications
4
45
0
Order By: Relevance
“…Among the metabolites, 7 were amino acids. Similar to our study, they found decreased lysine and tryptophan in cattle showing clinical signs of ketosis 19 . Not surprisingly, they found a relationship between glucogenic amino acids such as arginine, valine, and glycine which are processed into phosphoenolpyruvate to synthesize glucose, and clinical ketosis 28 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the metabolites, 7 were amino acids. Similar to our study, they found decreased lysine and tryptophan in cattle showing clinical signs of ketosis 19 . Not surprisingly, they found a relationship between glucogenic amino acids such as arginine, valine, and glycine which are processed into phosphoenolpyruvate to synthesize glucose, and clinical ketosis 28 .…”
Section: Discussionsupporting
confidence: 92%
“…Not surprisingly, they found a relationship between glucogenic amino acids such as arginine, valine, and glycine which are processed into phosphoenolpyruvate to synthesize glucose, and clinical ketosis 28 . They also found a correlation between clinical ketosis and the levels of ketogenic amino acids such as leucine and lysine, which can be converted to ketones in the liver 29 , and amino acids that are both glucogenic and ketogenic such as tryptophan and isoleucine 19,30 . These studies support amino acid levels in the blood plasma being dynamic and reflecting the metabolic status of the animal.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Holstein-Friesian cows, a milk glycerophosphocholine/phosphocholine ratio of 2.5 early in lactation was associated with a very low risk of developing ketosis (Klein et al 2012). Plasma metabolomic profiling was able to distinguish between lactating clinically normal cows, cows with subclinical ketosis, and cows with clinical ketosis (Zhang, Davis et al 2013;Li et al 2014;Sun et al 2014). Hepatic lipidosis could also be diagnosed using the plasma metabolome in transition Holstein-Friesian and Red-Holstein cows (Imhasly et al 2014) and early lactation Holstein-Friesian and Simmental cows (Humer et al 2016).…”
Section: Metabolome and Ketosismentioning
confidence: 99%
“…Although the correlation between excessive fat intake and non-alcoholic fatty liver disease in humans remains controversial [4] , its prevalence has continued to increase concomitant with the epidemic of obesity. In addition, a severe negative energy balance (NEB) during the early lactation period, as a consequence of insufficient energy intake to sustain the high energy requirements for milk production, can also cause fatty liver, especially in dairy cows [5][6][7] , thereby resulting in major economic losses to the dairy industry [8,9] . Although liver biopsy is the gold standard for assessment of fatty liver disease, the procedure is invasive and only evaluates approximately 0.002% of the liver parenchyma [10] .…”
Section: Introductionmentioning
confidence: 99%